BRAZILIAN INLAND WATER BIO-OPTICAL DATASET TO SUPPORT CARBON BUDGET STUDIES IN RESERVOIRS AS WELL AS ANTHROPOGENIC IMPACTS IN AMAZON FLOODPLAIN LAKES: PRELIMINARY RESULTS - Barbosa, C.; Novo, E.; Ferreira, R.; Carvalho, L.; Cairo, C.; Lopes, F.; Stech, J.; Alcantara, E. [UNESP]; Schreier, G.; Skrovseth, P. E.; Staudenrausch, H. (Copernicus Gesellschaft Mbh, 2015)
This work presents ongoing efforts and preliminary results for building a dataset that represents the first and most comprehensive bio-optical information available on Brazilian inland waters to support the development of remote sensing algorithms for monitoring aquatic systems. From 2012 to 2014 optical and limnological data was gathered along thirteen field campaigns in five Brazilian reservoirs, in an irrigation and domestic water supply reservoir located in semi-arid northeast of the country and in Amazonian floodplain lakes, thus covering the diversity of Brazilian inland waters. At each site 20 stations, on average, were sampled to acquire profiles of the following optical variables: absorption, attenuation, scattering, and backscattering coefficients and radiances/irradiances spectra above and in-water. Alongside these measurements, water samples were collected for determining concentrations of chlorophyll-a (Chl-a), Total Suspended Solid (TSS), Total Dissolved Carbon (TDC) and its organic/inorganic fractions, CDOM absorption, phytoplankton specific absorption [ aph*] and Non-Algal Particles absorption [ aNAP*]. Preliminary results show that Chl-a concentrations ranged from 0.6 to 243 mu g/L in reservoirs and 0.90 to 92 mu g/L in Amazonian lakes, while TSS concentrations ranged from 0.3 to 31mg/L in reservoirs and 0.5 to 162mg/L in Amazonian lakes. In situ beam attenuation coefficients ranged from 1.4 to 16m(-1) in reservoirs and 12.5 to 38m(-1) in Amazonian lakes, while diffuse attenuation coefficients of downwelling irradiance over the Photosynthetically Active Radiation (Kd(PAR)) extended from 0.35 to 4.5m(-1) in reservoirs and 1.69 to 13.30m(-1) in Amazonian lakes. Our research group is building this dataset anticipating future demands for algorithm validation regarding OLI/Landsat8 data and ESA Sentinel missions to be launched as of 2015.
Keywords: Brazilian inland waters; Amazon Floodplain Lake; bio-optical dataset; Inherent and Apparent optical measurements; Diffuse attenuation coefficient